Factors affecting decisions of farmers to produce geographical indication dry beans: a case from Turkey - Dogan, Nilgun; Adanacioglu, Hakan (Frontiers in Sustainable Food Systems, 2024)
Geographical Indicitaions (GIs) are defined as labels that show the relationship of a product with a certain region. They are of great importance in terms of distinguishing these products from the similar ones in terms of the quality that the characteristic features of the region bring to the product, making them stand out commercially, contributing to the rural development and preserving the cultural heritage. Dry beans cultivated by the farmers in the Gümüşhane province is newly recognized as a GI product that is unique in both taste and quality. This study is intended to identify the factors affecting the farmers' decision to produce GI-labelled dry beans. The survey was conducted in January-March 2021. A sampling size of the participants consisted of 50 farmers who cultivated GI-labelled dry beans and 50 non-GI dry beans. A binary logistic regression analysis approach was employed to identify the factors affecting the likelihood of the farmers cultivating the GI dry beans. The results of the model indicate that the young farmers with the low educational level, the low property land size, the low yield per decare, and the large farmland, the high annual agricultural income and specializing in the dry beans production are more likely to engage in the production of GI dry beans. For the farms involving the GI product, agricultural associations can be advised with the farmers with the wider agricultural acreage and the high annual agricultural income, and that specialize in the production of such products. The participation of the farmers in the agriculture enterprises involving the GI dry beans will depend on them seeing positive widespread effects, which requires a long-term commitment.